Facile Chan‐Lam coupling using ferrocene tethered N‐heterocyclic carbene‐copper complex anchored on graphene. (4th April 2019) - Gajare, Shivanand; Jagadale, Megha; Naikwade, Altafhusen; Bansode, Prakash; Rashinkar, Gajanan
Abstract : Ferrocene tethered N ‐heterocyclic carbene‐copper complex anchored on graphene ([GrFemImi]NHC@Cu complex) has been synthesized by covalent grafting of ferrocenyl ionic liquid in the matrix of graphene followed by metallation with copper (I) iodide. The [GrFemImi]NHC@Cu complex has been characterized by fourier transform infrared (FT‐IR), fourier transform Raman (FT‐Raman), CP‐MAS 13 C NMR spectroscopy, transmission electron microscopy (TEM), thermogravimetric analysis (TGA), energy dispersive X‐ray (EDX) analysis, X‐ray photoelectron spectroscopy (XPS), Brunauer–Emmett–Teller (BET) surface area analysis and X‐ray diffractometer (XRD) analysis. This novel complex served as a robust heterogeneous catalyst for the synthesis of bioactive N ‐aryl sulfonamides from variety of aryl boronic acids and sulfonyl azides in ethanol by Chan‐Lam coupling. Recyclability experiments were executed successfully for six consecutive runs. Abstract : Graphene supported ferrocene tethered N ‐heterocyclic carbene Cu (I) complex has been synthesized. The complex exhibited excellent activity in Chan‐Lam coupling reaction. Ease of separation and reusability of complex are key features of reported protocol.